Motivation and value of low-cost green car (LCGC) purchase intention across generations - Lorenza Kirana; Nila A. Windasari (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2019)
The low-cost green car (LCGC) is becoming one of interesting research topics in the automobile industry along with its unique characteristics of a vehicle product, tax incentives, and industry growth. The characteristics of this green product and its economic value are ultimately shifting customer behavior. Therefore, an understanding of the purchase motivation and value perception is crucial to determine the purchase intention. Perceived value acted as a full experience that customers received as a combination of thinking and feeling dimensions which are consistent with the utilitarian and hedonic motivations. Besides, LCGC sales have also been growing recently from the first car owner until more senior customers who are predicted to have different motivations and values across generations.This study explores the LCGC car purchase intention of 240 customers in Indonesia to find relationships of buyers' motivation and perceived value to the LCGC purchase intention across generations X, Y, and Z. The result shows that hedonic motivation significantly differs particularly between generation Y versus Z, and X versus Z. However, utilitarian motivation does not significantly differ among generations. Further, perceived value also significantly differs between generations X and Y.
Keywords: M30; M31; 650; customer motivation; hedonic; LCGC; perceived value; purchase intention; utilitarian